2019
DOI: 10.24198/pjd.vol31no3.25071
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between pediatric liquid medicines (PLMs) and dental caries in chronically ill children

Abstract: Introduction: Purpose of this research is to assess the relationship between long-term pediatric liquid medicines (PLMs) consumption and dental caries in 2–12-years-old chronically ill children. Methods: A cross-sectional study was performed in a public pediatric hospital in India for a period of 6 months. A total of 455 children aged 2–12 years old with various chronic diseases who were receiving PLMs for more than 6 months were selected as the subjects in this study and compared with 531 children of similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…45 Our study showed no significant difference in the amount of sugar content in longterm and short term ODTs which was like that reported by Siddiq et al The long-term use of ODTs can be a potential risk for the development of caries especially among children. 22,23 According to Passos et al only 5% sucrose concentration is required to form the cariogenic biofilm. 45 The majority of the ODTs contain carbohydrates as an excipient which plays a vital role in forming a tablet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…45 Our study showed no significant difference in the amount of sugar content in longterm and short term ODTs which was like that reported by Siddiq et al The long-term use of ODTs can be a potential risk for the development of caries especially among children. 22,23 According to Passos et al only 5% sucrose concentration is required to form the cariogenic biofilm. 45 The majority of the ODTs contain carbohydrates as an excipient which plays a vital role in forming a tablet.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] The routine use of LOMs and its relation to caries have been linked in numerous studies. [21][22][23][24] It is known that most of the common paediatric LOMs can cause dental erosion since their pH is below 5.5. 13,15,25 But the literature on ODT's erosive potential and sugar content in the Indian pharmaceutical market is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…45 Our study showed no significant difference in the amount of sugar content in longterm and short term ODTs which was like that reported by Siddiq et al 35 The long-term use of ODTs can be a potential risk for the development of caries especially among children. 22,23 According to Passos et al only 5% sucrose concentration is required to form the cariogenic biofilm. 45 The majority of the ODTs contain carbohydrates as an excipient which plays a vital role in forming a tablet.…”
Section: Discussionmentioning
confidence: 99%